Facility- and service-based competition and investment in fixed broadband networks: Lessons from a decade of access regulations in the European Union member states - Wolfgang Briglauer; Klaus Gugler; Adhurim Haxhimusa (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
This paper employs firm-level panel data of 57 incumbent and entrant firms for 23 European countries in the decade from 2003 to 2012. We examine the impact of service- and facility-based competition on firm-level investment as well as the strategic effects underlying infrastructure investment decisions. At the same time we explicitly model the structural dynamics of broadband investment by means of a flexible accelerator model. The empirical specification employs dynamic panel estimation techniques which allows us to account for various sources of endogeneity. We find that facility-based competition exerts a positive and significant impact on both incumbents and entrants implying that incumbents' and entrants' investment decisions are strategic complements. Moreover, we find that intermodal competition in terms of fixed-mobile substitution exerts different effects at the firm level. Finally, we show that service-based competition appears to have no significant impact on the investment decision of incumbents and entrants. However, with respect to the later phase of market liberalization, service-based competition exerts a negative impact on entrants' investment. Our results thus also provide relevant policy guidance on the role of service-based competition in regulating emerging high-speed broadband infrastructure.
urn:nbn:de:bsz:180-madoc-394977
Keywords: L43; L52; L96; 330; investment dynamics; regulation; service-based competition; facility-based competition; strategic effects